Effective Bioassay for Vinegar Production Using African Star Apple (Chrysophyllum albidum G. Don) by Enzymatic Catalysis and Acetic Bioconversion - VODOUNOU, Audray; ADJOU, EULOGE SÈNAN; CHOUGOUROU, CHÈPO DANIEL (My University, 2023)
The present study aims to valorize theneglected and underutilized fruits of Chrysophyllumalbidum in vinegar production through enzyme catalysisand acetic bioconversion. To do this, Chrysophyllumalbidum juice was extracted from ripe fruits by using apectinolytic enzyme (Pectinex Ultra SP-L) at aconcentration of 1ml.kg-1. The extracted juice was firstsubjected to alcoholic fermentation using yeast strains ofSaccharomyces cerevisiae in anaerobic conditions, andsecondly to an acetic fermentation using strains ofAcetobacter spp. isolated from unpasteurized cider vinegar.Results obtained indicated that the use of the pectinolyticenzyme significantly improves (p<5%) the yield of juiceextraction. The highest extraction yield (89.21%) isobtained with an incubation temperature of 60°C for 120minutes. The monitoring of kinetic parameters during thefermentation processes indicated a significant variation(p<5%) of the pH, the acidity, the density and the Brix ofthe musts during the bioprocesses. Vinegars produced hada pH of 3.83±0.12 and a relatively low acetic acid content(5.17±0.23 %), characteristic of vinegars for food use, inaccordance with European standards. The production ofvinegar from Chrysophyllum albidum fruit, using fast, lessexpensive and easily applicable processes, presents a veryinteresting solution to reduce postharvest losses, and couldmake available on national and international markets, anew bioproduct with high added value (8) (PDF) Effective Bioassay for Vinegar Production Using African Star Apple (Chrysophyllum albidum G. Don) by Enzymatic Catalysis and Acetic Bioconversion. Available from: https://www.researchgate.net/publication/373721777_Effective_Bioassay_for_Vinegar_Production_Using_African_Star_Apple_Chrysophyllum_albidum_G_Don_by_Enzymatic_Catalysis_and_Acetic_Bioconversion#fullTextFileContent [accessed Jan 20 2024].
Keywords: Chrysophyllum albidum; EnzymaticCatalysis; Alcoholic Fermentation; Acetic Fermentation; Vinegar